Fatwas on Inter-faith Marriage in Indonesia - Muhamad Ali (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2002)
This article presents a study on the fatwas (legal opinion) concerning inter faith marriage in Indonesia. The fatwas under the discussion are those issued by Nahdlatul Ulama (NU) and Majelis Ulama Indonesia (MUI) in post-Independence Indonesia. Those fatwas are of special significance, both in terms of Islamic legal discourses and -perhaps more importantly- Muslims' perceptions and attitudes towards other religious communities in Indonesia. Issued by authoritative bodies of Indonesian Islam, more in particular the NU, the fatwas could be said as presenting the voices of Indonesian Muslims in their encounters with the issues of religious tolerance and plurality.DOI: 10.15408/sdi.v9i3.658